PERTUMBUHAN EKONOMI INDONESIA DAN KETIMPANGAN JENDER SUATU ANALISIS RUNTUN WAKTU (TIME SERIES ANALYSIS) - Wilson Rajagukguk; Suzanna Yosephine Tobing; Melinda Malau (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
In Indonesia, there is still gender inequality in various forms, such as in education, remuneration, and position. The Government of Indonesia reports that Indonesian women still experience inequality in many aspects. In 2010, the mean years of schooling are longer for men than for women (8.34 versus 7.50 years). Only 17.5% of Indonesian women involved in Parliament and only 44% of women worked as a manager, professional, administrator or technician. A time series data will be used in this study. This study will regress growth rate of real gross domestic product (GDP) per capita on labor force growth, investment (gross total investment), trade openness and a composite index of gender inequality using a time series analysis. The results of the analysis show that gender inequality slows down the economic growth, while the investment, trade openness and growth of labor force accelerate the economic growth.